Analisis Pengaruh Bagi Hasil, Inflasi, Nilai Tukar, dan Bi-Rate Terhadap Dana Pihak Ketiga pada Bank Bjb Syariah - Nurhaya; Listian Indriyani Achmad; MH Ainulyaqin; Sarwo Edy (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study ed to determine the factors that influence third party funds. This type of research was quantitative research using secondary data in the form of time series data of 34 monthly samples from January 2019 to October 2021 with the object of bank bjb syariah. with Bank BJB Syariah research object, Data was processed using E-views software version 12. The research results ed that profit sharing and inflation had no partial effect on third party funds at Bank BJB Syariah, the exchange rate and the BI rate had a significant negative effect on funds. third parties at Bank Bjb Syariah, and together (simultaneously) profit sharing, inflation, exchange rate, and Bi rate affect third party funds at Bank Bjb Syariah.